Types and Patterns of Colonic Polyps Encountered at a Tertiary Care Center in a Developing Country in South Asia - Dakshitha Praneeth Wickramasinghe; Sanjeev F. Samaranayaka; Chamila Lakmal; Sashi Mathotaarachchi; Chula Kanishka Lal; Chathuranga Keppetiyagama; Dharmabandhu Nandadeva Samarasekera (Analytical Cellular Pathology)
Purpose. To identify the prevalence, types, and patterns of colonic polyps in a cohort of patients presenting to a tertiary care referral center in Sri Lanka. Methods. Endoscopy and pathology reports of a single unit from 2006 to 2013 were analyzed retrospectively. Spearman’s correlation coefficient and chi-square test were used to identify correlations. Results. There were a total of 158 patients (M : F, 10 : 57) who had polyps encountered on colonoscopy (n=1408) and flexible sigmoidoscopy (n=2402) with an incidence of 4.1%. Mean age was 56.5 years (SD 16.4) and the incidence of polyps increased with age. The majority (81.6%) had one polyp. A total of 188 polyps were assessed and most were seen in the rectum (33.5%) followed by sigmoid colon (22.9%). The commonest histological type was tubulovillous adenoma (33.5%) followed by tubular adenoma (24.5%). Most polyps were benign (91.5%). There was no statistically significant correlation with age or gender with malignancy, site, or histology. Discussion and Conclusion. The incidence of colorectal polyps was lower than the values reported in the west. More polyps were identified in males. There was no statistically significant association between age, gender, or multiplicity and malignant change in the polyps.